A scientometric study of the journal Profesional de la Información - Rodríguez-Faneca, Cristina; Maz-Machado, Alexander; Cuida, Astrid (Technium Social Sciences Journal, 2021)
Bibliometric studies provide researchers with varied and important information that allow to obtain different indicators and to understand relationships in the dissemination of science. In this work, we analyse the production of the journal Profesional de la Información, the first Spanish journal to be included in the Information Science & Library Science category of the Journal Citation Reports (JCR). We determined the degree of collaboration and identified the most productive authors of this journal. We found an increase in collaborative authorship and a stagnation of the journal in the third quartile of the JCR. Most of the papers published in the journal are produced in Spain.